2016
DOI: 10.1080/13696998.2016.1269774
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of insulin-related hypoglycemia in Denmark: an analysis using the Local Impact of Hypoglycemia Tool

Abstract: The LIHT highlights the substantial economic burden of insulin-related hypoglycemia in Denmark, and provides a means to estimate the savings that could be made by lowering hypoglycemia rates. For example, the costs associated with using a new insulin or introducing a patient education program could be offset with the cost saving from reducing hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Varying by ±20% the cost of a GP visit, the percentage of severe episodes treated in hospital for T1DM, and the percentage utilization for GP visits for a non-severe episode in T2DM had the largest effects on the overall results and therefore were the inputs that showed the greatest uncertainty. The cost and utilization of HCP visits (GP and diabetes specialist) were also among the main drivers of the model in an analysis conducted in the UK and Denmark [ 9 , 10 ]. In addition, a study (SECCAID) that estimated the costs of diabetes in Spain reported that 28% of the total corresponds to primary care [ 24 ], further supporting the fact that GP costs are an important part of the cost of diabetes and its associated complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying by ±20% the cost of a GP visit, the percentage of severe episodes treated in hospital for T1DM, and the percentage utilization for GP visits for a non-severe episode in T2DM had the largest effects on the overall results and therefore were the inputs that showed the greatest uncertainty. The cost and utilization of HCP visits (GP and diabetes specialist) were also among the main drivers of the model in an analysis conducted in the UK and Denmark [ 9 , 10 ]. In addition, a study (SECCAID) that estimated the costs of diabetes in Spain reported that 28% of the total corresponds to primary care [ 24 ], further supporting the fact that GP costs are an important part of the cost of diabetes and its associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoglycemia can result in visits to a general practitioner or diabetes specialist, and additional self-monitoring of blood glucose (SMBG) tests used to assess blood glucose levels following a hypoglycemic episode. These costs have previously been estimated for the UK and Denmark using the Local Impact of Hypoglycemia Tool (LIHT) [ 9 , 10 ]. The aim of this study was to use the LIHT to estimate the cost of insulin-related hypoglycemia in Spain, and to identify the potential cost savings associated with a reduction in hypoglycemia rates.…”
Section: Introductionmentioning
confidence: 99%
“…11 A number of costof-illness and cost-consequence studies have reported the direct medical costs incurred per severe hypoglycaemic episode across clinical characteristics in developed countries, including the USA, 12-14 the UK, 15,16 Denmark, 17 the Netherlands, 18 Germany, 7 Spain 19,20 and South Korea. 11 A number of costof-illness and cost-consequence studies have reported the direct medical costs incurred per severe hypoglycaemic episode across clinical characteristics in developed countries, including the USA, 12-14 the UK, 15,16 Denmark, 17 the Netherlands, 18 Germany, 7 Spain 19,20 and South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…On a global scale, SH imposes a substantial economic burden on national healthcare services, driven by an increasing need for blood glucose monitoring, emergency services, hospitalization and additional visits to doctors and allied health professionals. 11 A number of costof-illness and cost-consequence studies have reported the direct medical costs incurred per severe hypoglycaemic episode across clinical characteristics in developed countries, including the USA, [12][13][14] the UK, 15,16 Denmark, 17 the Netherlands, 18 Germany, 7 Spain 19,20 and South Korea. 21 While the mean costs of an SH episode can be estimated, there is a scarcity of information to date concerning costs during the preceding and subsequent years.…”
mentioning
confidence: 99%
See 1 more Smart Citation